Bushido and the art of living an inquiry into samurai values - Bennett, Alexander (2017)
"What is Bushido? What is Budo? How are the culture and traditions of the samurai connected with the modern martial arts? Is the ancient wisdom of Japan's feudal warriors truly relevant in the twenty-first century? If so, how can it be accessed? This book addresses these questions, and is a must read not only for martial artists, but also for those who want to know more about the enigmatic Japanese mind and notions of self-identity"--Back cover.
Introduction: ever-changing Bushido -- Zanshin: lingering mind and the essence of Bushido -- Koyo-gunkan and the ideal leader -- Dead ready to live: Hagakure and Budo-shoshinshu -- Live and let live: the life-giving sword -- Bushido: the dark and the light.
"Originally published in Japanese under the title Nihonjin no shiranai bushid?o, by Bungeishunju Ltd. in 2013"--Title page verso.
Includes bibliographical references (pages 170-172)
Japan Foundation
Translated from the original Japanese into English.
Keywords: Bushido; Samurai -- History; History